Effect of direct current electrical stimulation on osteogenic differentiation and calcium influx - Moon, Hyeyeon; Lee, Minseon; Kwon, Soonjo (The Korean journal of chemical engineering, 2023)
Electrical stimulation is effective for bone healing. Several studies have shown that electrical stimulation affects cell migration and proliferation. This study examined whether electrical stimulation enhances the osteogenic differentiation of mouse clonal mesenchymal stem cells (cMSCs). Mouse cMSCs were exposed to electrical stimulation at three different voltages (1 V/cm, 0.5 V/cm, and 0.05 V/cm) for one hour per day. The applied electrical stimulation did not affect the cell viability. The alkaline phosphatase (ALP) activity was increased significantly at day 14 after electrical stimulation with 0.5 V/cm for one hour per day. The genes related to osteogenic differentiation were examined at days three, seven, and 14 after exposure to the three electrical stimuli. Osteocalcin (OC) expression was increased dramatically under all three-voltage conditions. These increases were closely related to the electrically stimulated increases in the intracellular calcium concentrations, assessed by Fluo-4 AM on day 14 after exposure to 0.05 V/cm for one hour per day. Furthermore, the expression of calcineurin/NFAT pathway-related genes was upregulated significantly after electrical stimulation. Thus, electrical stimulation enhances the osteogenic differentiation of mouse cMSCs by increasing the intracellular calcium concentration.